Strategi MSDM sebagai Fondasi Pengembangan Entrepreneur Berbasis Teknologi: Sebuah Kajian Konseptual - Alfina Nur Jannah; Agung Winarno; Wening Patmi Rahayu (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
The development of digital technology has changed the way organizations and individuals develop businesses, making Human Resource Management (HRM) strategies essential in shaping technology-based entrepreneurs. The gap between the demand and availability of digital talent, as reported by Startup Genome (2024) and Kominfo (2023), highlights that the development of technology entrepreneurs relies not only on individual abilities but also on HRM systems capable of building digital competencies and digital agility. This study aims to analyze the role of HRM strategies in strengthening the capacity of technology entrepreneurs, as well as identifying key elements such as digital HRM and digital competencies. The research method uses a literature review, analyzing international journals, industry reports, and relevant academic sources. The analysis was conducted through content analysis to build a conceptual model of HRM strategies. The results show that the implementation of digital HRM, such as e-HRM, HRIS, and HR analytics, can enhance an organization's digital capabilities, speed up talent recruitment, and improve training and competency management effectiveness. Furthermore, the development of digital competencies through training and mentoring has been proven to enhance innovative abilities and the readiness of technology entrepreneurs. This research contributes theoretically by integrating the RBV theory, digital HRM, and entrepreneurial competencies into a conceptual framework, and practically, it serves as a reference for designing digital talent development strategies and technology-based entrepreneurial ecosystems.